İslam hukuk biliminde norm-amaç ilişkisi - Türcan, Talip; Kulan, Mesut (My University, 2016)
Talip Türcan'ın Norm-Purpose Relation in Islamic Law Science adlı eserinin tanıtımı.
Keywords: Talip TÜRCAN; Norm-Purpose Relation in Islamic Law Science